A Review On Artificial Ground Water Recharge. - ARUN YADAV.; ABHIJIT SONJE; DR. PRIYANKA MATHUR; DR. D.A. JAIN (International Journal of Pharma and Bio Sciences, 2012)
In recent years the availability of water is low in low rainfall areas of the country so that people in those areas largely depend upon ground water for agriculture and domestic use. So that to improve the ground water situation it is necessary to recharge depleted ground water artificially. Artificial ground water recharge is the process by which water from above surface is added to the saturated zone of an aquifer either directly or indirectly. Due to over-exploitation of ground water decrease in the level of ground water so that increase level of saline water in costal areas. To avoid this some of the techniques like Spreading method, Recharge shafts, Injection wells, Induced recharge, improved Land and Watershed management are employed. Selection of particular method depends upon Hydro geological studies, Hydrological studies, Hydrometeoro- logical studies, Soil infiltration studies of area and chemical quality of water. This paper discusses issues related to artificial ground water recharge.